NATO under Attack: Why the Western Alliance Can Fight Outnumbered and Win in Central Europe without Nuclear Weapons - Mellenthin, F. W. von (New York Duke University Press, 1984)
One of the authors here, Major General F.W. von Mellenthin, was a German officer during World War II. He fought in Russia, northern Africa and western France. In this book, he does not relish a nuclear war exploding across his beloved German homeland, which had been so ravished during WWII. I just make a note here to reference that about 15 years earlier, another German general, Hasso von Manteuffel, wrote a similar book: Alternative to Armageddon, with U.S. General White and Col. Yale. Mellenthin had been a staff officer to Manteuffel.
Keywords: Politics